Portrait of attendees of the Sons of Hermann Convention - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Portrait of attendees of the Sons of Hermann Convention. This fraternity was founded to provide a mutual protection society for German immigrants who faced ethnic and religious prejudice in the U.S. during the 19th and early 20th centuries.